LAG3 immune inhibitors: a novel strategy for melanoma treatment - Wu, Renzheng; Zeng, Mingtang; Zhang, Yuchen; He, Jianping (Frontiers in Oncology, 2024)
Melanoma, a highly aggressive skin cancer, poses significant challenges in treatment, particularly for advanced or metastatic cases. While immunotherapy, especially immune checkpoint inhibitors (ICIs) targeting CTLA-4 and PD-1, has transformed melanoma management, many patients experience limited responses or develop resistance, highlighting the need for new therapeutic strategies. Lymphocyte activation gene 3 (LAG-3) has emerged as a promising target in cancer immunotherapy. LAG-3 inhibitors have shown potential in restoring T cell functions and enhancing anti-tumor immunity, particularly when used in combination with existing ICIs. This review discusses the latest advancements in LAG-3 inhibition for advanced melanoma, emphasizing its role in overcoming resistance and improving patient outcomes.